Wireless telemedicine and m-health: technologies, applications and research issues. (5th October 2011) - Xiao, Yang; Takahashi, Daisuke; Liu, Jing; Deng, Hongmei; Zhang, Jingyuan
Telemedicine is not medicine, but it is used to compute, to communicate and to deliver high-quality medical care regardless of location. It reduces cost, time and resources. Furthermore, wireless technologies play significant roles in telemedicine, and they are therefore called wireless telemedicine or mobile-health. This paper provides a comprehensive survey on wireless telemedicine, including the relevant wireless technologies, applications and research issues.